The Impact of Maryam Exercise Towards the Stress Level and Cortisol Serum Level among Primiparous Pregnant Women - Maya Erisna; Runjati Runjati; Apoina Kartini; Mahalul Azam; Donny Kristanto Mulyantoro (International Journal of Nursing and Health Services (IJNHS), 2020)
Women are more at risk to stress in pregnancy than during the puerperium. One method of coping with stress is through physical exercise. Maryam Exercise can be used as an alternative to the development of pregnancy exercises in Indonesia because it covers the holistic aspects and easy to do. It is a combination of basic pregnancy exercises, Islamic prayer (Salat) movements and dhikr.  The purpose of this study was to examine the impact of Maryam exercise on the stress levels and cortisol serum levels among primiparous pregnant women. This study used a quasi-experimental study design, pre-test and post-test with non-equivalent control group. In the third trimester of 40 primiparous women  were randomly assigned into two groups such the experimental group (n=20) and the control group (n=20). The experimental group received the Maryam exercise while the control group received the standard antenatal exercise. There was a significant difference in stress levels between the intervention group and the control group before and after receiving the intervention (p <0.05). The cortisol levels also showed the significance difference between the intervention group and the control group before and after receiving the intervention (p <0.05). The findings of this study suggest that Maryam Exercise has a positive impact on stress levels and cortisol serum levels of primiparous pregnant women.